2013
DOI: 10.1302/0301-620x.95b8.31310
|View full text |Cite
|
Sign up to set email alerts
|

Is there reduced polyethylene wear and longer survival when using a mobile-bearing design in total knee replacement?

Abstract: The purpose of this study was to undertake a meta-analysis to determine whether there is lower polyethylene wear and longer survival when using mobile-bearing implants in total knee replacement when compared with fixed-bearing implants. Of 975 papers identified, 34 trials were eligible for data extraction and meta-analysis comprising 4754 patients (6861 knees). We found no statistically significant differences between the two designs in terms of the incidence of radiolucent lines, osteolysis, aseptic loosening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Attempting to solve these problems, the mobile-bearing (MB) designs were introduced. MB TKA designs were claimed to reduce the risk of aseptic loosening by minimizing the stress transmitted to the prothesis–bone interface, to reduce the wear of the PE insert by increasing the implant conformity [ 34 , 41 ], to increase the overall range of motion by allowing the femur to roll back during flexion and to rotate during extension and to reduce the anterior knee pain rates [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attempting to solve these problems, the mobile-bearing (MB) designs were introduced. MB TKA designs were claimed to reduce the risk of aseptic loosening by minimizing the stress transmitted to the prothesis–bone interface, to reduce the wear of the PE insert by increasing the implant conformity [ 34 , 41 ], to increase the overall range of motion by allowing the femur to roll back during flexion and to rotate during extension and to reduce the anterior knee pain rates [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Stipulated advantages of the mobilebearing system also appear to be conceptual only thus far, with several systematical reviews finding no statistical differences when compared to fixed-bearing systems in terms of clinical performance (clinical scores, range of motion, component alignment) as well as revision rates or adverse events. [10][11][12][13][14][15] Iliotibial band impingement following total knee replacement is not a novel occurrence. However, to the best of our knowledge, our case is the first in the reported literature to occur in the rotating platform total knee replacement.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the rotating platform mobile bearing implant is similar enough for the different individual devices that, for the most part, results can be generalized for the class in terms of outcome assessment. To date, most studies have suggested that there is no functional advantage to mobile bearing designs over fixed bearing designs [32][33][34][35][36].…”
Section: Continuedmentioning
confidence: 99%